1996
DOI: 10.1097/00001888-199606000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the informal curriculum and traineesʼ ethical choices

Abstract: In October 1995, the Association of American Medical Colleges held its first Conference on Students' and Residents' Ethical and Professional Development. In a plenary session and break-out sessions, the 150 participants, representing a wide variety of medical and professional specialties and roles, discussed the factors and programs that affect medical trainees' development of ethical and professional standards of behavior. The main challenge of addressing students' professional development is the enormous ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(101 citation statements)
references
References 0 publications
0
98
0
3
Order By: Relevance
“…4,8 None of these studies have dealt with surgical specialties. Hafferty and Franks 9 and Hundert et al 10 developed a taxonomy of ethics curricula that describes 3 overlapping spheres: (1) formal curricula: what is taught in the classroom; (2)informal curricula: unscripted ,adhoc interpersonal lessons about values and attitudes, learned from role-models and peers outside the classroom as a subset of the hidden curricula; and (3) hidden curricula: the sum of all the socializing influences imbedded in the organizational and institutional culture including tacit knowledge, or task-specific experiences that cannot easily be articulated or stored in documents.…”
Section: The Case: It Is July and David Junior Is A First-year Residmentioning
confidence: 98%
“…4,8 None of these studies have dealt with surgical specialties. Hafferty and Franks 9 and Hundert et al 10 developed a taxonomy of ethics curricula that describes 3 overlapping spheres: (1) formal curricula: what is taught in the classroom; (2)informal curricula: unscripted ,adhoc interpersonal lessons about values and attitudes, learned from role-models and peers outside the classroom as a subset of the hidden curricula; and (3) hidden curricula: the sum of all the socializing influences imbedded in the organizational and institutional culture including tacit knowledge, or task-specific experiences that cannot easily be articulated or stored in documents.…”
Section: The Case: It Is July and David Junior Is A First-year Residmentioning
confidence: 98%
“…23 Given that supervision is often residentinitiated, residents may fear they could be perceived as ''weak'' for contacting their supervising attending physician. This may influence their behavior and discourage attending physician-level contact during times of uncertainty.…”
Section: Superb/safety Modelmentioning
confidence: 99%
“…This process is often termed the ''hidden or informal curriculum.'' [41][42][43][44][45][46] We know that many of these influences are detrimental to personal growth and may negate professional values. [43][44][45][46][47][48][49][50][51][52] In a survey, a majority of medical students reported that their moral values had been eroded while functioning as clinical clerks.…”
Section: Importance Of Group Dynamics In the Learning Processmentioning
confidence: 99%